Is Multi-Drug Resistant Tuberculosis More Prevalent in HIV-Infected Patients in Korea? - Lee, Shinwon; Lee, Sun Hee; Mok, Jeong Ha; Lee, Su Jin; Kim, Kye-Hyung; Lee, Jeong Eun; Lee, Seung Geun; Chung, Joo Seop; Kwak, Ihm Soo (Yonsei medical journal, 2016)
The epidemiological synergy between human immunodeficiency virus (HIV) and tuberculosis (TB) is a major threat to public health. However, the association between HIV and multi-drug resistant tuberculosis (MDR-TB) is not clear. To explore the association between HIV and MDR-TB infection, a case-control study was performed in Korea. A total of 1606 culture-proven TB patients (45 HIV vs. 1561 non-HIV) from January 2006 to October 2014 were included in this analysis. MDR-TB rates were 11.1% and 8.2% in the HIV and non-HIV groups, respectively (p=0.42), thus indicating that MDR-TB was not significantly associated with HIV infection in Korea.